Advances and challenges in the treatment of esophageal cancer - Shiming He (Elsevier, 2021)
Esophageal cancer (EC) is one of the most common cancers with high morbidity and mortality rates. EC includes two histological subtypes, namely esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC). ESCC primarily occurs in East Asia, whereas EAC occurs in Western countries. The currently available treatment strategies for EC include surgery, chemotherapy, radiation therapy, molecular targeted therapy, and combinations thereof. However, the prognosis remains poor, and the overall five-year survival rate is very low. Therefore, achieving the goal of effective treatment remains challenging. In this review, we discuss the latest developments in chemotherapy and molecular targeted therapy for EC, and comprehensively analyze the application prospects and existing problems of immunotherapy. Collectively, this review aims to provide a better understanding of the currently available drugs through in-depth analysis, promote the development of new therapeutic agents, and eventually improve the treatment outcomes of patients with EC.